2019
DOI: 10.1002/aic.16531
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of H2O and SO2 on the simultaneous calcination/sulfation reaction in CFBs

Abstract: The combined effect of H2O and SO2 on the reaction kinetics and pore structure of limestone during simultaneous calcination/sulfation reactions under circulating fluidized bed (CFB) conditions was first studied in a constant‐temperature reactor. H2O can accelerate the sulfation reaction rate in the slow‐sulfation stage significantly but has a smaller effect in the fast‐sulfation stage. H2O can also accelerate the calcination of CaCO3, and should be considered as a catalyst, as the activation energy for the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Vicente et al also reported that QC was the only product in the NBD photoisomerization conducted with the use of batch photoreactors. If there were side reactions which are common in many chemical transformations, the treatment of kinetic model would be more complex, which may be relevant to solving the group of ordinary differentiate equations . For reaction kinetic models with single ordinary differentiate equations, there are mainly two methods, including integration and differentiation, to determine kinetic parameters .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vicente et al also reported that QC was the only product in the NBD photoisomerization conducted with the use of batch photoreactors. If there were side reactions which are common in many chemical transformations, the treatment of kinetic model would be more complex, which may be relevant to solving the group of ordinary differentiate equations . For reaction kinetic models with single ordinary differentiate equations, there are mainly two methods, including integration and differentiation, to determine kinetic parameters .…”
Section: Resultsmentioning
confidence: 99%
“…If there were side reactions which are common in many chemical transformations, the treatment of kinetic model would be more complex, which may be relevant to solving the group of ordinary differentiate equations. [48][49][50] For reaction kinetic models with single ordinary differentiate equations, there are mainly two methods, including integration and differentiation, to determine kinetic parameters. 51 When the conversion of reactants is relatively high, the integration method is well suitable to deal with experimental data.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…As CO 2 is dominate in the gas phase for oxy-fuel combustion flue gas, the formation of CaCO 3 cannot be avoided. However, CaCO 3 is reactive towards SO 2 [39,40], and therefore, CaCO 3 can be converted to CaSO 4 if enough reaction time is provided.…”
Section: C'mentioning
confidence: 99%
“…CaO, a widely used adsorbent, has been proven to be highly effective in SeO 2 capture in flue gas . According to previous research studies, water vapor is an important component in flue gas, which has been fully confirmed to be able to promote the adsorption of CO 2 or SO 2 by CaO. Based on experiments and kinetic study, Li proposed that H 2 O would decompose on the CaO surface to form superficial OH, which could greatly increase the adsorption capacity. According to experimental data and density functional theory (DFT) calculation, the proposition has been verified by our previous study and Yang’s study .…”
Section: Introductionmentioning
confidence: 99%